John Fiske’s Semiotic Analysis About Body Shaming in Imperfect Film - Martha Ayuzulki Zainiya; Nur Maghfirah Aesthetika (Indonesian Journal of Cultural and Community Development, 2022)
There are phenomena and cases of body shaming actions that occur in Indonesia in everyday life, especially for women who often experience it and become victims of body shaming. Some people regard this act as just a common joke. However, the act of body shaming is an action that can affect a person's mental and psychic. The film Imperfect is the best film in 2019 which presents a story about the body shaming act experienced by a woman. This study aims to identify and describe John Fiske's semiotic analysis of body shaming in the film Imperfect. This research method uses qualitative descriptive analysis with John Fiske's semiotic analysis, namely the level of reality, representation and ideology. The results of this study indicate the form of body shaming in the film Imperfect, from the level of reality, namely in appearance, in terms of behavior, dialogue, and make-up of players. The reality here is that there is an assessment of beauty standards against women and jealousy and envy of Rara. At the level of representation, taking pictures of the object as a whole. The ideological level in the film Imperfect is patriarchal culture.